Altered gut microbiota after traumatic splenectomy is associated with endotoxemia. Issue 1 (December 2018) - Zhu, Hua; Liu, Yang; Li, Shengda; Jin, Ye; Zhao, Lei; Zhao, Fuya; Feng, Jing; Yan, Wei; Wei, Yunwei
Abstract Splenectomy carries a long-term risk of postoperative infection, and the chronic, low-grade inflammation associated with endotoxemia may be related to the gut microbiota. In this study, to increase our understanding of the potential cause of the high rate of infection in postsplenectomy patients, we evaluated the differences in the gut microbiota and plasma lipopolysaccharide level of patients after splenectomy relative to those of healthy controls. Thirty-two patients having undergone splenectomy and 42 healthy individuals were enrolled into the splenectomy (SP) and healthy control (HC) groups, respectively. The SP group was subdivided into three subgroups according to the length of their postoperative time. Fecal samples were used for gut microbiota analysis via 16s rRNA gene sequencing, blood examinations and plasma lipopolysaccharide measurements were also taken. Significant differences were observed in gut microbiota composition with regard to the relative bacterial abundances of 2 phyla, 7 families, and 15 genera. The lipopolysaccharide level was significantly higher in the SP group than in the HC group and were negatively associated with five bacterial families with low abundance in the SP group. The degree of the microbiota alteration increased with the length of the postoperative time. The PICRUSt analysis showed that the relative abundances oflipopolysaccharide biosynthesis proteins andlipopolysaccharide biosynthesis pathways were higher in the SP group and were positively associated with the plasma lipopolysaccharide level. Significant alterations were observed in the gut microbiota of the splenectomized patients and were associated with plasma lipopolysaccharide level. Further studies are needed to verify whether such alterations after splenectomy are related to an increased risk of complications.